Use of solar radiation in the improvement of spring canola (Brassica napus L., Brassicaceae) yield influenced by nitrogen topdressing fertilization - Dalmago, Genei Antonio; Pinto, Daniele Gutterres; Fontana, Denise Cybis; Gouvêa, Jorge Alberto; Bergamaschi, Homero; Fochesatto, Elizandro; Santi, Anderson (Agrometeoros, 2018)
The objective of the present study was to quantify and evaluate the coefficients of interception, absorption, and use of photosynthetically active solar radiation (PAR), and its effects on grain yield (YLD) of spring canola influenced by N topdressing fertilization. Two experiments were performed in 2013 and 2014 using a randomized block design, with four replicates and five treatments of N: T1-T5 (10, 20, 40, 80, and 160 kg ha-1, respectively). Plant, PAR, and meteorological variables were measured. The lower PAR interception efficiency (εi) occurred in treatment T1. The range of light extinction coefficient (k) was of the 0.55 to 1.09. PAR absorption efficiency (εa) ranged from 86 to 93%, while the PAR use efficiency (RUE) ranging from 1.2 to to 3.7 g m-2 MJ-1. The mean N dose for maximum agronomic efficiency (MAE) for YLD was 99.3 kg ha-1. The YLD varied according to N treatments and was influenced by RUE, dry matter accumulated until flowering (DMF), dry matter after flowering (DMAF) and total dry matter (TDM). Nitrogen fertilization affects the balance of PAR and, consequently, the canola yield.